Frequency-tuned electromagnetic field therapy improves post-stroke motor function: A pilot randomized controlled trial - Weisinger, Batsheva; Pandey, Dharam P.; Saver, Jeffrey L.; Hochberg, Arielle; Bitton, Adina; Doniger, Glen M.; Lifshitz, Assaf; Vardi, Ofir; Shohami, Esther; Segal, Yaron; Reznik Balter, Shira; Djemal Kay, Yael; et al. (Frontiers in Neurology, 2022)
Background and purpose: Impaired upper extremity (UE) motor function is a common disability after ischemic stroke. Exposure to extremely low frequency and low intensity electromagnetic fields (ELF-EMF) in a frequency-specific manner (Electromagnetic Network Targeting Field therapy; ENTF therapy) is a non-invasive method available to a wide range of patients that may enhance neuroplasticity, potentially facilitating motor recovery. This study seeks to quantify the benefit of the ENTF therapy on UE motor function in a subacute ischemic stroke population. Methods: In a randomized, sham-controlled, double-blind trial, ischemic stroke patients in the subacute phase with moderately to severely impaired UE function were randomly allocated to active or sham treatment with a novel, non-invasive, brain computer interface-based, extremely low frequency and low intensity ENTF therapy (1-100 Hz, <1 G). Participants received 40 minutes of active ENTF or sham treatment five days/week for eight weeks; ~three out of the five treatments were accompanied by 10 minutes of concurrent physical/occupational therapy. Primary efficacy outcome was improvement on the Fugl-Meyer Assessment – Upper Extremity (FMA-UE) from baseline to end of treatment (8 weeks). Results: In the per protocol set (13 ENTF and 8 sham participants), mean age was 54.7 years (±15.0), 19% were female, baseline FMA-UE score was 23.7 (±11.0), and median time from stroke onset to first stimulation was 11 days (interquartile range (IQR) 8–15). Greater improvement on the FMA-UE from baseline to week 4 was seen with ENTF compared to sham stimulation, 23.2±14.1 vs. 9.6±9.0, p=0.007; baseline to week 8 improvement was 31.5±10.7 vs 23.1±14.1. Similar favorable effects at week 8 were observed for other UE and global disability assessments, including the Action Research Arm Test (Pinch, 13.4±5.6 vs. 5.3±6.5, p=0.008), Box and Blocks Test (affected hand, 22.5±12.4 vs. 8.5±8.6, p<0.0001), and modified Rankin Scale (-2.5±0.7 vs. -1.3±0.7, p=0.0005). No treatment-related adverse events were reported. Conclusions: ENTF stimulation in subacute ischemic stroke patients was associated with improved UE motor function and reduced overall disability, and results support its safe use in the indicated population. These results should be confirmed in larger multicenter studies. Unique identifier: NCT04039178 Registration-URL: https://clinicaltrials.gov/ct2/show/NCT04039178